2022
DOI: 10.1002/mgg3.1899
|View full text |Cite
|
Sign up to set email alerts
|

FINCA syndrome—Defining neurobehavioral phenotype in survivors into late childhood

Abstract: Fibrosis, neurodegeneration, and cerebral angiomatosis (FINCA) syndrome is a rare disease (OMIM #618278) with only 10 cases described until now from six families (Uusimaa et al. 2018;Brodsky et al., 2020, Rapp et al., 2021. The reported cases carry variants in NHL repeat containing two gene (NHLRC2) (Biterova et al., 2018).In the first report, released in 2018, three Finnish patients were described (Uusimaa et al., 2018). In the second one, published in 2020, one Ukrainian patient was reported (Brodsky et al.,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(17 citation statements)
references
References 18 publications
1
16
0
Order By: Relevance
“…Combining the clinical features of our five novel patients with the previously described 13 patients ( Uusimaa et al, 2018 ; Brodsky et al, 2020 ; Rapp et al, 2021 ; Badura-Stronka et al, 2022 ) reveals the following: 10 patients have been reported as being alive (age between 4 and 61 years at the time of the publication), while eight were deceased (age at death between 10 months and 2 years, 5 months). Eight of the 18 patients were male.…”
Section: Discussionmentioning
confidence: 67%
See 3 more Smart Citations
“…Combining the clinical features of our five novel patients with the previously described 13 patients ( Uusimaa et al, 2018 ; Brodsky et al, 2020 ; Rapp et al, 2021 ; Badura-Stronka et al, 2022 ) reveals the following: 10 patients have been reported as being alive (age between 4 and 61 years at the time of the publication), while eight were deceased (age at death between 10 months and 2 years, 5 months). Eight of the 18 patients were male.…”
Section: Discussionmentioning
confidence: 67%
“… Schematic representation of the NHLRC2 domain composition and amino acid substitutions identified from the FINCA patients. The patients reported here harbored variants presented above the corresponding domain; the variants presented in gray boxes have been described previously ( Uusimaa et al, 2018 ; Brodsky et al, 2020 ; Rapp et al, 2021 ; Badura-Stronka et al, 2022 ). …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…WES variants prioritization was performed as previously described. 7 In results, WES study in proband compound heterozygous variants in the SLC39A4 were identi ed (hg38 8:144414042-C > T, c.1203G > A NM_130849.4, p.(Trp401Ter) and hg38 8:144415989-C > T, c.295G > A, NM_130849.4, p.(Ala99Thr)) (Fig. 4).…”
Section: Case Report Methods and Resultsmentioning
confidence: 88%